Dental aerosols: microbial composition and spatial distribution - Zemouri, C. (J Oral Microbiol, 2020)
Background: High-speed dental instruments produce aerosols, which can contribute to the transmission of pathogenic microorganisms. The aim of this study is to describe the microbial load and – composition and spatial distribution of aerosols in dental clinics. Methods: In four dental clinics active and passive sampling methods were used before, during and after treatment and at different locations. Retrieved colony forming units (CFU) were sequenced for taxon identification. Results: The samples contained up to 655 CFU/plate/30 minutes and 418 CFU/m(3)/30 minutes during dental treatment for active and passive sampling, respectively. The level of contamination after treatment and at 1.5 m distance from the patient’s head was similar to the start of the day. The highest contamination was found at the patient’s chest area. The aerosols consisted of 52 different taxa from human origin and 36 from water. Conclusion: Contamination in dental clinics due to aerosols is mainly low, although high level of contamination with taxa from both human and water origin was found within 80 cm around the head of the patient. Our results stress the importance of infection control measures on surfaces in close proximity to the head of the patient as well as in dental water lines.